Individual Differences in Spontaneous Expressive Suppression Predict Amygdala Responses to Fearful Stimuli: The Role of Suppression Priming - Chen, Shengdong; Deng, Zhongyan; Xu, Yin; Long, Quanshan; Yang, Jiemin; Yuan, Jiajin (Frontiers in Psychology, 2017)
Though the spontaneous emotion regulation has received long discussions, few studies have explored the regulatory effects of spontaneous expressive suppression at the neural level. The functional magnetic resonance imaging (fMRI) study aimed to examine whether individual differences in the tendency to use suppression manifests in decreased amygdala responses when individuals are spontaneously confronted with negative situations in Chinese culture valuing emotion suppression. Twenty-three heathy Chinese undergraduates completed a fMRI paradigm involving fear processing, and a synonym matching task was added to prime participants with the unconscious (automatic) expressive suppression goal. Participants completed measures of typical emotion regulation use (reappraisal and suppression), trait anxiety, and neuroticism. Results indicated that only in emotion suppression prime condition, greater use of suppression in everyday life was related to decreased amygdala activity. These associations were not attributable to variation in trait anxiety, neuroticism, or the habitual use of reappraisal. These findings suggest that 1) though Chinese cultures value emotion suppression, the regulatory effects of spontaneous suppression depends on the situational factors; 2) like spontaneous reappraisal, individual differences in suppression use are associated with decreased activation in ventral emotion generative regions in response to negative stimuli.